An investigation of factors affecting SMEs performance: an Indonesian case - Cahya Mukti Dwi Kurnia; Edy Raharja; Yohanes Sugiarto (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
The objectives of this paper is to investigate factors that affecting SMEs performance. Particularly, our study examined the effect of entrepreneurial orientation, adaptability to external environment, and competitive advantage to SMEs performance. We also test the effect of entrepreneurial orientation and adaptability to external environment on SMEs competitive advantage. Results of structural equation modeling on 100 SMEs in Semarang, Central Java, Indonesia, suggested that entrepreneurial orientation and competitive advantage has a positive effect on SMEs business performance. However, our prediction that adaptability to external environment positively affect SMEs performance was not supported. Furthermore, our study also found that entrepreneurial orientation and adaptability to external environment positively affect SMEs competitive advantage.